Comparative study of purification methods for influenza-specific IgY from chicken eggs - W. P. Rachmawan; M. E. Saputri; A. Esfandiari; R. D. Soejoedono; O. N. Poetri; B. F. Prasetyo (Bulgarian Journal of Veterinary Medicine)
Chicken eggs are widely used for different purposes including as a source of specific immunoglobulin (IgY). Therefore, this study aimed to evaluate various purification methods for influenza-specific IgY from chicken egg yolk. Three laying hens were vaccinated with an influenza vaccine. Influenza-specific IgY was purified from the chicken egg yolk using four different purification techniques in-cluding (1) water-soluble sodium chloride (WS-NaCl), (2) water-soluble polyethylene glycol (WS-PEG), (3) WS-PEG-ammonium sulfate (WS-PEG-AS) precipitation, and (4) a commercial IgY purifi-cation kit. These methods were compared in terms of protein concentration, IgY structure, and speci-ficity against the influenza virus. The results showed that all purification methods successfully ob-tained influenza-specific IgY, as confirmed by the agar gel precipitation (AGP) test against influenza antigen. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis showed that the WS-PEG precipitation method was unable to purify the entire IgY structure, while the other three methods were successful. The highest protein concentration was obtained using the commercial kit (9.931±0.214 mg/mL), followed by the WS-NaCl method (6.944±0.979 mg/mL). Although the commercial kit yielded the highest protein concentration, it may not be cost-effective for large-scale IgY production. The WS-NaCl method appeared to be a promising and feasible option for generating large quantities of IgY from chicken eggs.